Settlement of Intellectual Property Disputes through Arbitration in Indonesia - Pratama, Gede Aditya; Ni Luh Sukma Imagy; Ni Komang Darmiati; I Nyoman Tri Darma Gunawan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The continual advancement of technology and the expanding array of human needs have fuelled significant growth within the trade sector, particularly in intellectual property (IP) domains. This growth is evidenced by a marked increase in intellectual property registrations, which play a pivotal role in the trade sector. The surge in registrations, including trademark, copyright, patent, and industrial design sectors, has correspondingly led to a rise in intellectual property disputes. While these disputes traditionally find resolution within Commercial Courts, alternative mechanisms such as mediation and arbitration have gained prominence. The World Intellectual Property Organization (WIPO) oversees a specialized institution for mediation and arbitration, namely the WIPO Mediation and Arbitration Centre. Indonesia similarly hosts its own institution dedicated to resolving intellectual property disputes, the Intellectual Property Arbitration and Mediation Agency (BAM HKI), established in 2011. Arbitration mechanisms prioritize privacy, efficiency, and expediency in resolving intellectual property disputes compared to Commercial Courts. Consequently, the presence of arbitration institution offers a viable alternative dispute resolution mechanism favoured by involved parties.